Kerusuhan Massa oleh Supporter Persebaya - Didik Wahyudi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
Football supporters are the twelfth players who are arguably the most fanatical and enthusiastic in defending the club they love. Unfortunately, when they support their team, sometimes they commit mass riots by committing criminal acts as the destruction of property, ill-treatment, and humiliation. This paper aims to find out (1) how the mass riots transpired by PERSEBAYA Supporters and (2) how the juridical perspective and Islamic criminal law against the mass riots. At the end of the paper, two things were concluded. Firstly, that the mass riots committed by PERSEBAYA's Supporters in Surabaya were triggered by excessive fanaticism. Secondly, according to Islamic criminal law, it is included in the category of criminal acts of injury, torture, and vandalism, whether intentionally or intentionally. The reason for legal responsibility is because the Persebaya Supporter riots producing harm unto others and this must be legally processed either Islamic law or Positive law.